MANAGEMENT OF LEARNING AFTER THE COVID-19 PANDEMIC AT THE KUSUMA NEGARA COLLEGE OF TEACHER TRAINING AND EDUCATION (STKIP) - JAKARTA - Eka Rista Harimurti; Megawati Megawati; Muhammad Awin Alaby (Jurnal Scientia, 2023)
This article aims to provide an overview of learning management after the Covid – 19 pandemic at STKIP Kusuma Negara- Jakarta. This research took the locus at STKIP Kusuma Negara- Jakarta. The research used is qualitative research with the case study method which aims to explore information related to the conditions and problems of learning management to provide an overview of how learning is managed post-pandemic Covid – 19 at STKIP Kusuma Negara- Jakarta. Data support is obtained through data sources, namely observation (direct observation), interviews and documentation. The study results show that: (1) post – Covid – 19 learning planning at STKIP Kusuma Negara- Jakarta is carried out with learning plans and lecture contracts. (2) Implementing post-pandemic Covid – 19 learning at STKIP Kusuma Negara- Jakarta takes place online and offline by applying blended learning and hybrid learning methods. (3) post-pandemic Covid – 19 learning supervision at STKIP Kusuma Negara- Jakarta is carried out by monitoring learning processes, learning assessment and outcomes.